Identification of Formalin Content on Jambal Roti Salted Fish at Traditional Markets, North Surabaya, Indonesia - Ratna Yulistiani; Jariyah; Yunita Satya Pratiwi; Dianita Kumalasari; Agi Ramadhan (Nusantara Science and Technology Proceedings, 2024)
Jambal Roti, a well-known salted fish delicacy in Indonesia, has become a subject of concern due to reports of formaldehyde contamination. This research was conducted to investigate the presence of formaldehyde in Jambal Roti sold in traditional markets in North Surabaya and to analyze the physical characteristics of the contaminated fish. Using a descriptive research design with a survey approach, a total of 23 samples were collected and tested. The results showed that six samples, or 26%, contained formal--dehyde, with concentrations ranging from 0.125 ppm to 1.071 ppm. The highest formaldehyde level was found in sample JR18. The physical examination of contaminated samples revealed distinct characteristics that set them apart from uncontaminated ones. These samples had a firmer and more resilient texture, making them less susceptible to damage. In terms of appearance, they exhibited a paler yet more vibrant color compared to normal Jambal Roti. Moreover, the typical salty aroma that is characteristic of this fish was noticeably absent in the contaminated samples. These findings suggest that formaldehyde not only poses a health risk but also alters the physical and sensory qualities of Jambal Roti, affecting its overall quality as a food product. The presence of formaldehyde in food products is a serious concern, as it compromises both consumer safety and the reputation of the product. This study underscores the importance of stricter monitoring and regulation of food safety in traditional markets to prevent the distribution of contaminated food items like Jambal Roti, ensuring that consumers are not exposed to harmful chemicals.